The auto-call as an impactful technical tool in increasing adherence to lipid-lowering therapy and patient outcome in ambulatory settings: 1-year experience at tertiary cardiology center. (25th November 2020) - Fofanova, T.V; Smirnova, M.D; Ageev, F.T
Abstract: Background: Long-term adherence to lipid-lowering treatment is a challenge. Purpose: To develop a technical tool, an auto-call program, aimed to increase patient adherence to lipid-lowering therapy, and patient outcome in ambulatory care. Methods: 919 ambulatory patients were studied, divided to three groups: with low or moderate risk of developing atherosclerosis complications (Group 1); with high or very high risk of atherosclerosis complications, but without coronary artery disease (CAD) symptoms (Group 2); patients with symptomatic CAD (Group 3). At baseline, patients were invited to participate in the auto-call program (call-reminder to take the medication); the duration of study was 1 year. 663 patients (71.3%) consented to auto-calls received, 256 patients (28.7%) declined auto-calls. These two groups were comparable according to age, gender, the presence of comorbidities, the level of baseline adherence to lipid-lowering therapy, and the level of anxiety and depression. Treatment adherence was evaluated using Morisky-Green Medication Adherence Scale. Results: Group 1. After 1 year, the auto-call group showed a significantly higher degree of decrease in low-density lipoprotein cholesterol, LDL-C (p=0.001) and triglyceride, TG (p=0.002), and increase in high-density lipoprotein cholesterol, HDL-C (p=0.03) compared to the auto-call rejection group. Group 2. After 1 year, the auto-call group showed a significantly higher degree of decrease in total cholesterol, TC (p<0.02) and LDL-C (p<0.01), and increase in HDL-C (p=0.2) compared to the auto-call rejection group. Moreover, in the auto-call group, the baseline TC level was higher (6.4±1.5 mmol/l vs 6.0±1.4 mmol/l, p=0.03). Group 3. After 1 year, the auto-call group showed a significantly higher degree of decrease in TC (p<0.005) and TG (p<0.05). The degree of decline in LDL-C was higher in the auto-call group (−25.9 (−27.3; −17.0) vs −20.1 (−21.3; −0.2), however, non-significant. After 1 year, treatment adherence increased in the total cohort from 1.91 score (1.80; 2.02) to 2.6 score (2.52; 2.80), p<0.000001. However, in Group 3, a significant increase in scores from 2.0 (1.9; 2.2) to 3.0 (2.6; 3.1) was observed only in the auto-call group (p<0.00001). In Group 1 and Group 2, the increase in adherence did not depend on the presence or absence of auto-calls. It should be noted that adherence to therapy in patients of Group 3 was significantly higher at baseline (2.0 (1.9; 2.2) than in Group 1 (1.7 (1.6; 1.9), p<0.005) and Group 2 (1.9 (1.7; 2.1), p<0.05), respectively. Conclusions: Utilizing a high-tech auto-call reminder tool in patients with hyperlipidemia and CAD was associated with increased adherence to lipid-lowering therapy, which, in turn, resulted in significant decrease in LDL-C compared to patients who declined to participate in the auto-call program. Funding Acknowledgement: Type of funding source: None